Does privatizing advisory services guarantee better services? Evidence from advisory services pertaining to cocoa certification in Côte d'Ivoire. Issue 3 (27th May 2021) - Gboko, Kouamé Casimir; Faure, Guy; Ruf, François
ABSTRACT: Purpose: This study investigated the impact of privatization of advisory services on the quality of the services. Design/methodology/approach: The front- and back-office dimensions of advisory activities were analyzed through interviews with 43 advisers involved in the advisory services provided as part of a cocoa exporter's certification program. Findings: Our results showed that the ratio of advisors per producer in the private advisory system is too high, and the means of transport for advisors are inadequate. The training received by the advisors is strongly oriented towards mastering technical subjects related to certification requirements, while soft or process topics that would provide them with knowledge and skills required to co-produce with farmers is neglected. Regarding the front office dimension, advice to cocoa producers is largely prescriptive and fails to co-produce knowledge that is relevant to their needs. Practical implications: The study produced empirical data that allows us to go beyond the theoretical farm advice approach derived from micro-economic modeling. Theoretical implications: Our findings weaken the arguments in favor of privatization of farm advisory services. Originality/value: The study provides insights into the consequence of privatizing farm advisory services in the West Africa context by producing one of the first study on this subject in Côte d'Ivoire.